The abused woman a survivor therapy approach - Walker, Lenore, E.; WhiteBirch Producations (Princeton, N.J. : Films for the Humanities, 1995)
In this program, internationally-acclaimed psychologist and expert witness, Lenore Walker demonstrates the course of therapy with a middle-class, 35 year old woman who has a history of childhood sexual abuse and battering by her current husband. Illustrates the effectiveness of the survivor therapy approach, which combines interventions derived from both feminist and post-traumatic stress disorder approaches
Title from title screen
Script, Julie Stockler ; music, Dave Holland ; executive producer, Lilian Schein ; production manager, Joshua Holland ; produced and directed by John Holland ; editorial consultants: Suzanne Boyll, Barbara Brown, Arthur Freeman, Leo Goldberger, Beverly Greene, Susan Heitler
Cast: Laura Tietjen, Dr. Lenore Walker
DVD format
Keywords: Abused women -- Treatment; Women -- Psychology; Post-traumatic stress disorder -- Treatment; Feminist therapy; Psychotherapy